Credit Agreement and Notary-PPAT Responsibilities for Deed of Mortgage - Muhammad Azka Faizan; Achmad Sulchan (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
Banks are one financial institution that has an important role in the economy of a country. The problems in this study are (1) What are the factors that hamper the credit agreement and the responsibility of the Notary-PPAT in making the Deed of Granting Mortgage to the BPD Bank of Central Java?, 2) What is the legal consequence if the Notary-PPAT is late in making the Deed of Granting Mortgage to Bank BPD Central Java?, 3) How is the settlement if the Notary-PPAT is late in making the Deed of Granting Mortgage to the Bank BPD Central Java? The method used is the sociological juridical approach, the research specification is analytical descriptive. The results of this study are (1) The cost of increasing SKMHT to APHT because the process of certification of SKMHT objects that have not been registered requires expensive costs. 2) Based on that, SKMHT needs to be regenerated if APHT is to be made. 3) By making a new Power of Attorney Charge (SKMHT), which of course must be with the approval of creditors and debtors.